Validation of a P2Y12-receptor specific whole blood platelet aggregation assay. (2nd October 2016) - Amann, Michael; Ferenc, Miroslaw; Valina, Christian M.; Bömicke, Timo; Stratz, Christian; Leggewie, Stefan; Trenk, Dietmar; Neumann, Franz-Josef; Hochholzer, Willibald
Abstract: Testing of P2Y12 -receptor antagonist effects can support clinical decision-making. However, most platelet function assays use only ADP as agonist which is not P2Y12 -receptor specific. For this reason P2Y12 -receptor specific assays have been developed by adding prostaglandin E1 (PGE1) to reduce ADP-induced platelet activation via the P2Y1 -receptor. The present study sought to evaluate a P2Y12 -receptor specific assay for determination of pharmacodynamic and clinical outcomes. This study enrolled 400 patients undergoing coronary stenting after loading with clopidogrel or prasugrel. ADP-induced platelet reactivity was assessed by whole blood aggregometry at multiple time points with a standard ADP assay (ADPtest) and a P2Y12 -receptor specific assay (ADPtest HS, both run on Multiplate Analyzer, Roche Diagnostics). Patients were clinically followed for 1 month and all events adjudicated by an independent committee. In total, 2084 pairs of test results of ADPtest and ADPtest HS were available showing a strong correlation between results of both assays ( r = 0.96, p < 0.001). These findings prevailed in multiple prespecified subgroups (e.g., age; body mass index; diabetes). Calculated cutoffs for ADPtest HS and the established cutoffs of ADPtest showed a substantial agreement for prediction of ischemic and hemorrhagic events with a Cohen's κ of 0.66 and 0.66, respectively. The P2Y12 -receptor specific ADPtest HS assay appears similarly predictive for pharmacodynamic and clinical outcomes as compared to the established ADPtest assay indicating its applicability for clinical use. Further evaluation in large cohorts is needed to determine if P2Y12 -receptor specific testing offers any advantage for prediction of clinical outcome.